Integrated watershed management for natural resource conservation and livelihood security in semi-arid tropics of India - PALSANIYA, D R; SINGH, RAMESH; TEWARI, R K; YADAV, R S; DHYANI, S K (The Indian Journal of Agricultural Sciences, 2012)
Present study was undertaken during 2005–06 to 2009–10 to assess the impact of integrated watershed management interventions, viz soil and water conservation measures, agroforestry development, crop demonstrations with improved package of practices, plantation and human resource development on natural resource conservation and livelihood security in Garhkundar–Dabar watershed. Soil and water conservation measures generated 25 thousand cubic m water storage capacity, reduced number of dry wells to 2 % from 86 %, increased average available water column depth in wells from 0.88 m to 4.36 m and enhanced water availability to round-the-year from four to five months during the study period. Runoff per unit area and soil loss from treated watershed was 46 and 42.2 % lower than the untreated watershed respectively in 2009. The average productivity of major crops and cropping intensity increased by 26 and 119.5% respectively in 2009–10 as compared to 2005–06. The fodder availability increased by 208 % and within four years, watershed became a fodder secure area with fodder surplus of 1.992 tonne/year/animal as compared to (-) 0.569 tonne/year/animal in 2005–06. The increased direct and indirect employment opportunities in watershed reduced migration to 9% in 2009–10 from 29% in 2007–08.